Analisis Mengenai Hubungan Obesitas, Aktivitas Fisik, dan Stres Kerja Dengan Kejadian Hipertensi Pada Guru SMA Negeri di Kecamatan Kota Kabupaten Sumenep - Syarofatul Imamah; Irma Prasetyowati; Ruli Bahyu Antika (Jurnal Kesehatan Masyarakat, 2023)
Hypertension is known as "The Silent Killer" and causes many deaths. Riskesdas 2018 stated that hypertension in the population aged 18 increased from 26.2% in 2013 to 36.3% in 2018. Based on data from the Sumenep Health Office, it was stated that the prevalence of hypertension has increased from 2019 to 2020. This study aims to analyze the association between obesity, physical activity, and work stress with the incidence of hypertension among high school teachers in the Sub-District of Sumenep Regency. This research was a quantitative analytic study with a cross-sectional research design. Respondents in this research were high school teachers in the Sub-District of Sumenep Regency. The sample was 59 respondents used the multistage random sampling technique with proportional random sampling and simple random sampling. This research used sphygmomanometer digital, scales, microtoice, Baecke Questionnaire, and HARS (Hamilton Anxiety and Rating Scale). The analysis used was Chi-Square test. Based on the study's result, it can be concluded that physical activity (p-value = 0.039) is associated with the incidence of hypertension in high school teachers. There was a significant association between physical activity and the incidence of hypertension in high school teachers.